The Principles of Balance and Justice in Islamic Financial Institutions in Aceh: Opportunities, Challenges, and Strategies - Maulana, Nora; Safwan; Razali; N, Zahrum; Arif, Muhammad Tarmizi Bin Shamshul (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to examine the implementation of the concepts of balance and justice in Islamic financial institutions in Aceh, focusing on their role in promoting not only economic benefits but also fairness and social welfare. Using a qualitative descriptive approach supported by field data and document analysis, the research explores the opportunities and challenges encountered in operationalizing these values. The findings reveal several opportunities, including enhanced public trust, local economic development, and increased financial system stability and resilience. However, the study also identifies significant challenges such as limited public understanding and education, inadequate infrastructure and technology use, shortage of qualified human resources, suboptimal regulatory oversight, competition with conventional financial institutions, socio-cultural constraints, and difficulties in product implementation. To address these issues, the study proposes several strategies: adherence to sharia principles in operations and transactions, comprehensive sharia-based supervision, community outreach and education, collaborative initiatives with governmental bodies, innovation in sharia-compliant financial products, robust risk management, and a firm commitment to social responsibility. Contribution: This study contributes to the discourse on Islamic finance by emphasizing the practical integration of maqashid al-shariah in institutional governance. It also provides insights for policymakers and practitioners seeking to strengthen the role of Islamic financial institutions in achieving socio-economic justice in regional contexts.